The Belief in the Ancestral Cult of Childless Heroes in Fairy Tales - Mamatkulova Feruza Tohirovna (Research Parks Publishing LLC, 2021)
The article notes that the motive of infertility is one of the elements of the epic plot, in which specific interpretations of this element are motivated in Uzbek folklore as the formation of a fetus as a result of eating barley, corn stalks, apples, skull powder and other things, especially the strange old man (dervish, kalandar, the motive for the appearance of a fetus due to a strange apple given by a bearded enlightened old man, Hizr, etc.) at noon or on the right is thought to be one of the ancient and common elements of the magical tales of the Turkic peoples.